ANALYSIS OF PEDAGOGICAL AND PROFESSIONAL COMPETENCIES AND THEIR RELATIONSHIP WITH THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN PARIGI MOUTONG DISTRICT - Putu Budi Antara; Samsurizal M. Suleman; Agus Joko Purwanto (SOSIOEDUKASI, 2025)
This study investigated the influence of pedagogical and professional competence on teacher performance in elementary schools across Parigi Moutong Regency. Recognising the importance of these competencies in maintaining teaching effectiveness, this research examines their crucial role in the educational landscape. Employing a quantitative research design with a survey method, data were collected from a sample of 127 elementary school teachers selected from a population of 1,685 teachers in Parigi Moutong Regency. A questionnaire, distributed via Google Forms, was used to gather data on pedagogical competence, professional competence, and teacher performance. The collected data were analysed using multiple regression analysis, specifically the F-test, to determine the simultaneous influence of the independent variables on the dependent variable. The results of the analysis revealed a significant positive influence of both pedagogical and professional competence on teacher performance in the elementary schools of Parigi Moutong Regency. This is evidenced by a significance value of 0.000 (<0.05) for the combined effect of pedagogical and professional competence, and an F-statistic of 40.666, which is greater than the F-table value of 3.06. The findings underscore the critical importance of pedagogical and professional competencies in supporting effective teacher performance. This suggests that investments in enhancing these competencies can significantly contribute to maintaining the quality of education. A limitation of this study is its reliance on self-reported data, which may be subject to bias. Additionally, the cross-sectional design limits the ability to establish causal relationships definitively. Future research could explore these relationships longitudinally and incorporate qualitative data for a richer understanding